TEACHER PRACTICE IN AN INQUIRY-BASED MATHEMATICS CLASSROOM - Menezes, Luís (2012)
This paper presents a framework for an inquiry-based approach to mathematics teaching. It was developed by combining theoretical perspectives and case studies of experienced teacher that usually conduct inquiry based teaching of mathematics. This framework describes the actions teachers intentionally perform with two identified purposes: to promote the mathematical learning of the students and to manage the students and the class as a whole.